Carl Diem's "Organisation plan for Physical Education in Bulgaria" 1937 = "Plan de organización de la educación física en Bulgaria" de Carl Diem, 1937 - Jörg Schenk (Universidad Politécnica de Madrid, 2023)
Abstract In the middle of the 1930s, sport in young Bulgaria was in a deficient state not only in the eyes of its government, but also in those of foreign observers. The "Law on the Physical Education of Youth", passed in 1931, did not seem to fulfill the expectations placed in it, which is why the government asked for advice and the preparation of a general plan by an expert to be sent by the German Reich. Carl Diem, internationally known and respected at least since the 1936 Olympic Games, stayed in the country in the fall of 1937 and drafted the requested plan, which contained a concept for the future organisation of national sports, the construction of sports facilities and the training of "gymnastics teachers" on more than 60 pages, including annexes and an analysis of the current situation. The present study attempts a synoptic-descriptive presentation of this "Organisation Plan for Physical Education in Bulgaria", which was groundbreaking for national sports.   Resumen A mediados de los años 30, el deporte en la joven Bulgaria no sólo era deficitario a ojos de su gobierno, sino también de los observadores extranjeros. La "Ley de Educación Física de la Juventud" aprobada en 1931 no parecía cumplir las expectativas depositadas en ella, por lo que el gobierno solicitó el asesoramiento y la elaboración de un plan general por parte de un experto que sería enviado por el Reich alemán. Carl Diem, conocido y respetado internacionalmente desde los Juegos Olímpicos de 1936 a más tardar, estuvo en el país en otoño de 1937 y redactó el plan solicitado, que contenía un concepto para la futura organización del deporte nacional, la construcción de instalaciones deportivas y la formación de "profesores de gimnasia" en más de 60 páginas, incluyendo anexos y un análisis de la situación actual. El presente estudio intenta hacer una presentación sinóptica-descriptiva de este "Plan para la Educación Física en Bulgaria", que fue pionero para el deporte nacional.